Harvesting energy potential from air conditioner compressor of hot gas receiver tank using thermoelectric generator - Alsabahi, Hanaa Kadhim Kareem (2016)
Fire safety signage like emergency light and exit sign that are used all year round at buildings consume electricity for operation of signage and must function during emergency situation, therefore this can be costly in terms of maintenance cost. The DC voltage that is generated by thermoelectric generator (TEGs) is enough to operate this signage as alternative for its original batteries. The facilities and state institutions as well as residential complexes are using large numbers of air conditioner units. The air conditioner hot receiver tank rejects large amount of waste heat to the environment. The aim of this study is concerned with experimental test for (TEG) circuit arrangement for reducing waste heat by converting waste heat into electrical power. Specific objectives are to determine the primary design of TEG parameters with high power efficiency, which is able to produce ≥ 4 volt, then to verify the primary design results with experimental validation. Also, the research study the effect of weather properties on the cooling process of TEG. The system has built-in the electrical circuit as a battery charger to save (DC) electrical energy for operate four pieces of 12V LED in a (KELUAR) sign. Figure of Merit (FOM) and heat transfer approach based on the first law of thermodynamics are considered in arrangement of TEG. A total of 18 pieces of thermoelectric generator with dimensions of (40 mm × 40 mm × 3.4mm) with Bismuth Telluride inside material are fixed on aluminum frame which carries thermoelectric generator and sandwiched between air conditioner hot gas receiver tank and cool heat sink. Double heat sink per one thermoelectric generator piece are used to improve heat transfer. The TEG are arranged in three lines, each line consists of 6 pieces of TEGs connected in series to increase voltage, while the three lines of TEGs are connected in parallel to increase amount of power current. Electrical circuit built for charging 3.5V battery and connected with (KELUAR) sign lights was successfully fabricated. The circuit equipped with two convertor, (0.9V to 5V DC-DC) convertor for increase voltage. The experimental test shows that the output electrical power is extremely dependent on weather properties e.g ambient temperature, air velocity and relative humidity (RH), and it shows that the maximum open circuit voltage obtained in this research is 5.16V at 0.17m/s of air velocity, 73% of RH and 30.4 ℃ of ambient temperature. Experimental result shows that the maximum thermoelectric generator efficiency is 46% at temperature difference of 29.2℃ and dimensionless Figure of Merit ≃1. The system is able to harvest waste heat into electricity (DC) and charge the battery which serves as reservoir.